2017
DOI: 10.1038/sj.bdj.2017.224
|View full text |Cite
|
Sign up to set email alerts
|

Evidence summary: the relationship between oral and cardiovascular disease

Abstract: Aim This paper reports on one review of four rapid reviews undertaken to explore the relationships between oral health and general medical conditions, in order to support teams within Public Health England, health practitioners and policy makers. This review aimed to explore the most contemporary evidence on whether poor oral health and cardiovascular disease occurs in the same individuals or populations, to outline the nature of the relationship between these two health outcomes and to discuss the implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 24 publications
0
90
0
5
Order By: Relevance
“…In older adults, poor oral health has been associated with numerous diseases, including cardiovascular disease, respiratory disease, and diabetes, as well as incident frailty . Frailty is a clinical state in which there is an increase in an individualʼs vulnerability for developing dependency and/or mortality when exposed to a stressor .…”
mentioning
confidence: 99%
“…In older adults, poor oral health has been associated with numerous diseases, including cardiovascular disease, respiratory disease, and diabetes, as well as incident frailty . Frailty is a clinical state in which there is an increase in an individualʼs vulnerability for developing dependency and/or mortality when exposed to a stressor .…”
mentioning
confidence: 99%
“…In addition to bacterial components (e.g., lipopolysaccharide or LPS), periodontal disease allows locally‐produced proinflammatory mediators (e.g., interleukin‐(IL‐1) 1β, tumor necrosis factor‐α (TNF‐α), IL‐6, and prostaglandin E2 (PGE2)) to pour into the bloodstream, initiating responses in more distant tissues (Gemmell, Marshall, & Seymour, ; Loos, ; Loos, Craandijk, Hoek, Wertheim‐van Dillen, & van der Velden, ; Moutsopoulos & Madianos, ). The dissemination of bacteria and their biproducts into the bloodstream have the added effect of inducing system‐level infection responses that may instigate or affect the progression of cardiovascular diseases (for reviews of the evidence, see Dietrich, Sharma, Walter, Weston, & Beck, ; Dietrich et al, ), chronic obstructive pulmonary disease (Liu et al, ; Wang et al, ; Zeng et al, ), pneumonia (Awano et al, ; El Attar, Zaghloul, & El Menoufy, ; Scannapieco & Mylotte, ; Sharma & Shamsuddin, ; Terpenning et al, ), and diabetes (Bissett, Stone, Rapley, & Preshaw, ; Borgnakke, Ylöstalo, Taylor, & Genco, ; Lalla et al, ; Nelson et al, ; Taylor, Burt, Becker, Genco, & Shlossman, ). For example, platelet aggregation can be induced by oral bacteria such as P. gingivalis and S. sanguis or by the proinflammatory immune cytokines generated in response to them, affecting the formation of thrombi in the arteries and veins (Herzberg & Meyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that oral health complications, such as inflammation and infections that begin in the mouth, can lead to major health complications (e.g., dental abscess) [2]. Furthermore, a growing body of research has identified a potential connection between oral health and other chronic conditions, such as diabetes and cardiovascular diseases [3][4][5]. The National Academy of Medicine (an American nonprofit, non-governmental organization providing expert advice on issues relating to health, medicine, and health policy) has proposed integrating oral health into primary care as a way to expand access to recommended treatments and promote better health overall [6,7].…”
Section: Introductionmentioning
confidence: 99%